2017
DOI: 10.7554/elife.29388
|View full text |Cite
|
Sign up to set email alerts
|

CHIP as a membrane-shuttling proteostasis sensor

Abstract: Cells respond to protein misfolding and aggregation in the cytosol by adjusting gene transcription and a number of post-transcriptional processes. In parallel to functional reactions, cellular structure changes as well; however, the mechanisms underlying the early adaptation of cellular compartments to cytosolic protein misfolding are less clear. Here we show that the mammalian ubiquitin ligase C-terminal Hsp70-interacting protein (CHIP), if freed from chaperones during acute stress, can dock on cellular membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Likewise, previous proteomics identified ANXA5 (0.45-fold), HLA-B (0.22-fold) — as well as, FLNA (that here was below the level of detection by immunoblot but significantly changed in the MS analysis) — as putative CHIP substrates using an orthogonal substrate identification approach ( Bhuripanyo et al., 2018 ). Additionally, AHNAK (0.33-fold) is present in proteomics focused on the CHIP-interactome ( Kopp et al, 2017 ). (Note that all fold changes stated are derived from our proteomic screen).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, previous proteomics identified ANXA5 (0.45-fold), HLA-B (0.22-fold) — as well as, FLNA (that here was below the level of detection by immunoblot but significantly changed in the MS analysis) — as putative CHIP substrates using an orthogonal substrate identification approach ( Bhuripanyo et al., 2018 ). Additionally, AHNAK (0.33-fold) is present in proteomics focused on the CHIP-interactome ( Kopp et al, 2017 ). (Note that all fold changes stated are derived from our proteomic screen).…”
Section: Resultsmentioning
confidence: 99%
“…The latter, however, only occurs in the absence of cellular stress ( Tawo et al., 2017 ). Also recently, it has been shown that CHIP can be transiently recruited to cellular membranes, having affinity for specific phospholipid species ( Kopp et al, 2017 ). CHIP localization to membranes is shown to be HSP70-independent, again pointing to a non-canonical function for CHIP in membrane protein regulation.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 K170 mediates the susceptibility to protein degradation in the absence of CHIP. These results suggest that another E3 ligase may be involved in SIRT6 ubiquitination . One of the potential mechanisms for CHIP regulation of the aging process may be through maintaining SIRT6 protein stability, allowing SIRT6 to participate in histone deacetylation and DNA repair activities.…”
Section: Chip Regulation Of Agingmentioning
confidence: 87%
“…CHIP‐K30A, which has a mutation in its chaperone‐binding domain, fails to recognize substrate proteins, suggesting that CHIP interacts with its substrates through the participation of chaperone protein . Although CHIP usually interacts with its substrates through a chaperone protein, it occasionally interacts with substrate proteins in a chaperone‐independent manner (Table ) …”
Section: Chip Functions As An E3 Ligasementioning
confidence: 99%
See 1 more Smart Citation